Innovation in Public Service Delivery in Terms of Shared Services Centres in Local Governments: A Case Study of the City of Toruń (Poland) - Gawłowski, Robert; Modrzyński, Paweł (Journal of Public Governance, 2020)
Objectives: The public sector has been subjected to financial pressure. One of the tools to improve the environment of the public sector entities and introduce greater management flexibility in governance is establishing Shared Services Centres (SSCs).Research: The article presents a case study regarding the implementation process and the effectiveness assessment of this solution based on the example of the city of Toruń.Research Design & Methods: The paper provides a case study of SSC of the city of Toruń.Findings: Based on the results, it can be concluded that the key barrier to the implementation of SSCs as the innovation tool of public management is the lack of understanding of business management tools among directors of public sector units that were not involved in the issue of management efficiency.Implications / Recommendations: What appears to be the most challenging is the sociological factor that matters in terms of SSCs implementation. Social capital of the units’ directors, trust, and reciprocity is much more important than institutional arrangements.Contribution / Value Added: The paper shows the first evaluation of SSC in local government in Poland based on a case study. It is believed that this approach might be very fruitful for further theoretical research and practical implementation. Article classification: research article